PENGEMBANGAN APLIKASI BELAJAR MATEMATIKA KONTEKSTUAL BERBASIS ANDROID DENGAN METODE WATERFALL - Maulidyawati, Desi; Widiarta, I Made; Aqmalia, Afridha Nia (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
The development of information technology encourages teachers and educational practitioners to make adjustments to the ways and methods of student learning. Students who are social creatures, of course, also feel the impact of these technological developments. One of them is gadget. It is not uncommon for students to neglect their duties as a student due to the preoccupation with playing gadgets. Therefore, it is necessary if students are facilitated so that they can learn in a fun way as if they are playing gadgets. This android-based contextual math learning application is designed using the waterfall method, which consists of several math materials including: multiplication, division, fractions, square, rectangle and comparison. The activities in the application are designed to guide students to discover (guided discovery) math concepts. The goal is to provide meaningful learning experiences and experience in solving non-routine (contextual) problems. This application has been tested on 43 users including students and teachers. From the interview results, it is known that the application can be an alternative that can be used by students to learn math concepts. An attractive and contextual display provides a positive response by users regarding the application that has been developed.